Simulation of four quadrant fuzzy logic controlled matrix converter fed DC motor - Ruksana, S. K.; Pavan, Kumar Karedla; Sai, Goutham K. (I-Manager's Journal on Electrical Engineering, 2025)
This paper presents the concepts of a single-phase matrix converter as a universal converter for the four-quadrant operation of a DC motor. The Matrix converter is implemented as a rectifier, chopper, inverter and cyclo-converter for a high frequency step down has been presented in this paper. This will reduce the need for a new or extra converter. The technique used for the implementation of the proposed topology was sinusoidal pulse width modulation technique. This paper verifies the four possible conversion processes say AC-DC, DC-DC, DC-AC and AC-AC from a high frequency input to the desired low frequency output by the single phase matrix converter alone. The results of the four conversion topologies along with the filter has been presented in this paper. The proposed topology has been implemented in the MATLAB/SIMULINK software and the desired results for each of the converter topology has been verified